ChemInform Abstract: Oxidative Nucleophilic Aromatic Amination of Nitrobenzenes. Issue 40 (16th September 2016) - Khutorianskyi, V. V.; Sonawane, M.; Posta, M.; Klepetarova, B.; Beier, P.
Abstract: The oxidative nucleophilic aromatic amination of nitrobenzenes (II) and (IV) with lithium salts of arylamines (I) leads to N‐aryl‐2‐nitroanilines.